Predicting athletic success motivation using mental skills and emotional intelligence and its components in male athletes - Kajbafnezhad, H.; Ahadi, H.; Heidarie, A.; Askari, P.; Enay, M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to predict athletic success motivation by mental skills, emotional intelligence and its components. METHODS: The research sample consisted of 153 male athletes who were selected through random multistage sampling. The subjects completed the Mental Skills Questionnaire, Bar-On Emotional Intelligence questionnaire and the perception of sport success questionnaire. Data were analyzed using Pearson correlation coefficient and multiple regressions. RESULT: Regression analysis shows that between the two variables of mental skill and emotional intelligence, mental skill is the best predictor for athletic success motivation and has a better ability to predict the success rate of the participants. Regression analysis results showed that among all the components of emotional intelligence, self-respect had a significantly higher ability to predict athletic success motivation. CONCLUSION: The use of psychological skills and emotional intelligence as an mediating and regulating factor and organizer cause leads to improved performance and can not only can to help athletes in making suitable and effective decisions for reaching a desired goal.